THE RELATIONSHIP OF FAMILY SUPPORT WITH COMPLIANCE WITH A LOW SALT DIET IN HYPERTENSION PATIENTS IN POSBINDU KEMUNING, MARGAHAYU DISTRICT, BEKASI CITY, 2023 - Wulandari, Cindi; Simamora, Rotua Suriany Simamora; Dinda Nur Fajri (Jurnal Medicare, 2024)
Hypertension or high blood pressure is a condition in which blood pressure is above the normal limit of 120/80 mmHg. The normal limit of blood pressure is less than 130/85 mmHg. If the blood pressure is more than 140/90 mmHg then it is declared hypertension. This study aims to determine the relationship between family support and low-salt diet adherence in hypertensive patients at Posbindu Kemuning, Margahayu Village, Bekasi City in 2023. The research method used is quantitative with crossectional analytical research type.The population in this study was hypertensive patients at productive age, aged 15-64 years at Posbindu Kemuning, Margahayu Village, totaling 90 people. Data collection technique using a simple type of random sampling based on inclusion criteria and obtained a sample of 73 respondents. The results of the study found that with a significant level of 95% or a value of α 5% (0.05) the Chi Square test results obtained p-value (0.000   ) < a value of α (0.05). This indicates that H0 is rejected. The conclusion of the study is that there is a relationship between family support and adherence to a low-salt diet in people with hypertension at Posbindu Kemuning, Margahayu Village, Bekasi City in 2023.